The Naturalness Level of Terrestrial Areas in Bartin Province (Northern Türkiye) - Duran, Celalettin (Journal of Anatolian Environmental and Animal Sciences, 2025)
The level of naturalness of terrestrial ecosystems is the degree to which they are exposed to human influence. The high level of naturalness reflects low human impact and high biodiversity. Determining the level of naturalness of terrestrial ecosystems is extremely important for long-term land planning and conservation, sustainability, and resource management. This study examined the naturalness level of natural/anthropogenic areas within the administrative borders of Bartin province. Six spatial factors were used. These are settlement density, population density, road density, land cover/use, Normalized Difference Vegetation Index (NDVI), and Topographic Roughness Index (TRI). These six essential factors were inverted into the spatial fuzzy memberships using Geographic Information Systems (GIS). A final map was obtained by overlaying the fuzzy memberships in the fuzzy overlay model (FOM). According to this resulting map, the city center and its surroundings have a high anthropogenic impact and a low level of naturalness. The Kure Mountains National Park (KMNP) in the east of the province and the rugged mountain ranges in the south have a high level of naturalness, being remote from anthropogenic impact. Anthropogenic land degradation has expanded due to road construction, mining, and forestry activities. Uncontrolled economic activities constitute potential areas of human-induced degradation.